Modified Sistrunk's Operation - Baskota, DK (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Key words: thyroglossal cyst/fistula; Sistrunk's operation; modified Sistrunk operation; body of hyoidDOI: 10.3126/njenthns.v1i1.4738 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.34-35